An Experimental Study on the Deformation Behavior of Aluminium Armour Plates Impacted by Two Different Non-deformable Projectiles - Jena P.K.; Savio S.G.; Kumar K.S.; Madhu V.; Mandal R.K.; Singh A.K. (My University, 2025)
The present study describes the experimental results pertinent to the penetration of AA-2024, AA-6061 and AA-7017 plates with two different non-deformable steel projectiles. The diameters of the projectiles used for ballistic impact testing are 7.62 and 12.7 mm. The projectiles are impacted on the aluminium targets of 70 mm thickness with velocities in the range of 840±10 m/s. The results presented include variation in damage pattern in experimental alloys with respect to different projectiles. The microstructures and micro-hardness values along the projectile penetration path have been investigated to understand the material deformation behaviour. Some observations relating to the adiabatic shear band formation have also been presented. From the ballistic testing experiments, it is observed that AA-7017 plates display higher ballistic resistance among the tested aluminium alloys. The ballistic performance of the aluminium alloy plates have been correlated with their respective mechanical properties. © 2017 The Authors.